Recommendations for Preventing Land Degradation Processes (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
In the article, land degradation, its causes, the status of the works being carried out to prevent these processes and, in turn, suggestions and recommendations are mentioned.